Lettering at the entrance gateway of Grand Hotel - Ghosh, Ayan (2023)
The opening of the Suez Canal in 1869 resulted in shorter travel time from India to Europe, revolutionizing the maritime trade in India. Improved connectivity also brought more European tourists to Mumbai, and they stayed at the Grand Hotel, located close to Ballard Pier, from where ships disembarked passengers.